Analisis Faktor yang Mempengaruhi Siklus Menstruasi Berbasis Teori Handerson pada Remaja Putri di SMA 10 Kota Semarang - Adelia Wahmi Amanda; Sri Wahyuni; Tutik Rahayu (Journal of Health, Medical, and Psychological Studies, 2025)
This study aimed to analyze factors influencing menstrual cycle regularity among adolescent girls using Virginia Henderson’s basic needs theory framework. A quantitative correlational design with a cross-sectional approach was conducted among 128 tenth-grade students at a public senior high school in Semarang, Indonesia. Biological, psychological, sociological, and spiritual variables were assessed using validated instruments, and data were analyzed through chi-square tests and multivariate logistic regression. The findings indicate that menstrual cycle regularity is not determined by a single factor but reflects the interaction of multiple unmet basic needs. Sleep quality and physical activity emerged as the most dominant predictors, while nutritional status and stress showed indirect effects after controlling for other variables. These results suggest that lifestyle-related needs play a central role in maintaining reproductive health during adolescence. The application of Henderson’s theory provides a comprehensive explanatory model by linking physiological regulation with daily functional behaviors. This study contributes empirically to adolescent reproductive health research by demonstrating the relevance of a nursing-based theoretical framework in identifying dominant determinants of menstrual health and informing school-based health promotion strategies.